A comparison of whole-body vibration and resistance training on total work in the rotator cuff - Hand, J.; Verscheure, S.; Osternig, L. (Journal of Athletic Training, 2009)
We found no difference in strength gains between the whole-body vibration and resistance training and the resistance training-only groups. It may be possible to indirectly strengthen the rotator cuff using a multijoint dynamic resistance training program. Research on whole-body vibration is in its infancy and should continue so that we can learn if this technique is a useful precursor to resistance training